Assessing the recovery from prerenal and renal acute kidney injury after treatment with single herbal medicine via activity of the biomarkers HMGB1, NGAL and KIM-1 in kidney proximal tubular cells treated by cisplatin with different doses and exposure times - Sung-Man Oh; Gunhyuk Park; Seung Hoon Lee; Chang-Seob Seo; Hyeun-Kyoo Shin; Dal-Seok Oh (BMC, 2017)
Abstract Background Acute kidney injury (AKI) is an initial factor in many kidney disorders. Pre- and intra-renal AKI biomarkers have recently been reported. Recovery from AKI by herbal medicine has rarely been reported. Thus, this study aimed to investigate the dose- and time-dependent effects of herbal medicines to protect against AKI in cisplatin-induced human kidney 2 (HK-2) cells by assessing the activities of high-mobility group box protein 1 (HMGB1), neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1). Methods Proximal tubular HK-2 cell lines were treated with either 400 μM of cisplatin for 6 h or 10 μM of cisplatin for 24 h and then exposed to ten types of single herbal medicines, including Nelumbo nymphaea (NY) at a dose of 100 μg/mL. The AKI biomarkers HMGB1, NGAL and KIM-1 were repeatedly measured by an ELISA assay at 2, 4, and 6 h in the group treated with 400 μM of cisplatin to confirm necrotic cell death and at 6, 24, and 48 h in the group treated with 10 μM of cisplatin to examine apoptotic cell death. Recovery confirm was conducted through in vivo study using ICR mice for 3 day NY or Paeonia suffruticosa intake. Results Cisplatin treatment at a concentration of 10 μM decreased cell viability. Treatment with 400 μM of cisplatin reduced HMBG1 activity and resulted in lactate dehydrogenase release. In longer exposure durations (up to 48 h), NGAL and KIM-1 exhibited activity from 24 h onward. Additionally, NY treatment resulted in an approximately 50% change in all three biomarkers. The time-dependent profiles of HMGB1, NGAL and KIM-1 activities up to 48 h were notably different; HMGB1 exhibited a 7-fold change at 6 h, and NGAL and KIM-1 exhibited 1.7-fold changes at 24 h, respectively. Consistently, serum and urine NGAL and KIM-1 activities were all reduced in ICR mice. Conclusions Several single herbal medicines, including NY, have a potential as effectors of AKI due to their ability to inhibit the activation of HMGB1, NGAL and KIM-1 in an in vitro AKI-mimicked condition and simple in vivo confirm. Furthermore, an in vivo proof-of-concept study is needed.